Clinical Features and Analysis in Pituitary Stalk Interruption Syndrome - Qiuxuan Guo; Jing Zhao; Shuang Yu (International Journal of Endocrinology)
Objective. Pituitary stalk interruption syndrome (PSIS) is characterized by the absence of pituitary stalk, pituitary hypoplasia, and ectopic posterior pituitary. Because the etiology and clinical cognition of PSIS remain elusive, we analyzed the clinical features of PSIS in Chinese patients. Methods. A retrospective analysis was conducted on the clinical presentation, laboratory data, imaging examination, and management of 24 PSIS inpatients from our center over 10 years. Results. Among the 24 PSIS patients, there were 22 males (91.7%) and 2 females (8.3%). Growth hormone deficiency was present in all 24 cases (100%), hypogonadism in 24 cases (100%), secondary adrenal insufficiency in 22 cases (91.2%), and hypothyroidism in 21 cases (87.5%). 20 cases (83.3%) of PSIS patients exhibited deficiencies in four anterior pituitary hormones, 3 cases (12.5%) exhibited deficiencies in three anterior pituitary hormones, and 1 case (4.2%) exhibited deficiencies in two anterior pituitary hormones, with none exhibiting deficiencies in posterior pituitary hormones. Among the 24 PSIS patients, 12 had a history of growth hormone therapy before admission, and 12 had no such history. Additionally, 19 cases (79.2%) with PSIS were complicated by dyslipidemia, 15 cases (62.5%) were complicated by nonalcoholic fatty liver disease, and 9 cases (37.5%) were complicated by hyperuricemia. Conclusions. PSIS often presents with growth retardation and hypogonadotropic hypogonadism, but in some cases, short stature is not exhibited. PSIS is prone to complications such as dyslipidemia, nonalcoholic fatty liver disease, and hyperuricemia, increasing the risk of cardiovascular and cerebrovascular diseases. In clinical practice, the diagnostic ability of PSIS should be improved, and pituitary function and complications should be evaluated in a timely manner to avoid delayed treatment.